2021
DOI: 10.1111/iere.12541
|View full text |Cite
|
Sign up to set email alerts
|

The Brexit Vote, Inflation and U.K. Living Standards

Abstract: This article studies how voting for Brexit affected living standards in the United Kingdom. Using heterogeneity in exposure to import costs across product groups, we analyze how the depreciation of sterling caused by the referendum affected consumer prices. We find that the Brexit depreciation led to higher inflation in product groups with greater import shares in consumer expenditure. Our results are consistent with complete pass-through of import costs to consumer prices and imply aggregate exchange rate pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…When prices adjust, there should be no di¤erence, but even after they do, Gopinath et al (2010) show 7 Distribution costs paid in local currency are not a¤ected by exchange rate movements and thus reduce exchange rate pass-through into consumer prices. 8 There is evidence showing that the increase in in ‡ation in the UK after Brexit was mostly due to increases in the prices of goods more exposed, directly or indirectly via inputs, to imports (Hobijn et al, 2019;Breinlich et al, 2017). that there is still a large di¤erence in pass-through, which is estimated at 0.84 for exports of goods priced in the producer's currency and at 0.25 for goods priced in the importer's currency.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…When prices adjust, there should be no di¤erence, but even after they do, Gopinath et al (2010) show 7 Distribution costs paid in local currency are not a¤ected by exchange rate movements and thus reduce exchange rate pass-through into consumer prices. 8 There is evidence showing that the increase in in ‡ation in the UK after Brexit was mostly due to increases in the prices of goods more exposed, directly or indirectly via inputs, to imports (Hobijn et al, 2019;Breinlich et al, 2017). that there is still a large di¤erence in pass-through, which is estimated at 0.84 for exports of goods priced in the producer's currency and at 0.25 for goods priced in the importer's currency.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Immediately after the Brexit referendum, the Pound Sterling had a sharp depreciation by 15% against a trade weighted basket of currencies, and in particular vis-a-vis the Euro. This depreciation made foreign imported products more expensive, affecting inflation and living standards in the UK as demonstrated by Breinlich et al (2017). However, it might have boosted UK exporters' performance in international markets, by reducing the cost of their goods for foreign buyers.…”
Section: Methodsmentioning
confidence: 99%
“…A first group of studies has modelled ex-ante the Brexit economic effect and its macroeconomic cost, predicting a reduction in trade and in GDP growth in multiple scenarios (Born et al 2017, Dhingra et al 2017, Sampson 2017. Secondly, several papers have analysed the first effects of the Brexit referendum, finding evidence of a reduction in UK living standards as a consequence of the related significant exchange rate shift (Kren 2017, Breinlich et al 2017, of negative reactions to stock market fluctuations in certain industrial sectors (Ramiah et al 2017), showing the impact on firms' financing decisions (Berg et al 2019), and on their labour demand (Javorcik et al 2019).…”
mentioning
confidence: 99%
“…The negative impact of inflation in Africa is reflected in the high cost of borrowing (Agoba et al, 2020b; Ikeda, 2021), high cost of living (Breinlich et al, 2017), and high levels of poverty (Meo et al, 2018). Many scholars have found that high inflation negatively affects poverty.…”
Section: Introductionmentioning
confidence: 99%